Growth of Galactomyces geotrichum in sequencing batch reactors under different organic loading conditions - Matos, M. (2011)
The present work aims to study the effect of the organic loading rate on the growth of filamentous fungi. For this purpose, three sequencing batch reactors (SBR), fed with an easy biodegradable substrate (acetate), were operated at different organic loading rates: 4.3 g COD L -1 day-1 (SBR1), 1.0 g COD L-1 day-1 (SBR2) and 0.5 g COD L-1 day-1 (SBR3). High amounts of fungal filaments were observed in the SBR operating at higher organic loading rate, as ascertained by direct microscopic inspection, while, at lower organic loading rates, overabundance of fungal filaments was not observed. Sequence retrieved from the isolated fungal filaments presented high similarity (99 %) to Galactomyces geotrichum.